YOUNG LEARNERS’ ENGAGEMENT IN SPEAKING ACTIVITY TAUGHT BY USING GAME - Nafisah, Nailin; Kurniati, Diah; Rokhayani, Atik (SIMPLE: International Journal of English Education, 2024)
The researchers found problems with the focus of the seventh-grade students at one of the Islamic Boarding School in Kudus, they often did not listen to lessons which made them lack vocabulary and have difficulty speaking English. The purpose of this research was to To explore the seventh-grade students’ engagement in speaking activity taught by using game. The design of the research was qualitative research with the seventh-grade students of the Islamic Boarding School in Kudus as the participants. The instrument of this research was an observation checklist which was adapted from the International Center for Leadership in Education (ICLE) with consists of five aspects that are related to learner engagement, each aspect consists of several Likert-type format statements which required a numerical scale varying from 1 through 4, namely (1) is a rating of low, (2) medium, (3) good, and (4) very good.. The result of the research presents that students’ engagement in speaking activity taught by using game  shows a high criteria.